2014
DOI: 10.3390/f5122980
|View full text |Cite
|
Sign up to set email alerts
|

Former Land Use and Host Genotype Influence the Mycorrhizal Colonization of Poplar Roots

Abstract: Abstract:The present paper analyses the community structure of ectomycorrhiza (ECM) and arbuscular mycorrhiza (AM) fungi associated with seven different poplar clone types growing in a patch system on soil from four different former land use types, originating from spruce forest, poplar stand, grassland and cornfield. We determined the extent to which ECM and AM play a role on the studied factors (genotype, former land use type and host growth). The diversity of ECM and AM fungal communities was estimated by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Similar to the total species richness estimates, diversity estimates based on the Shannon index of AM fungi (Honnay et al 2017), ECM fungi and total fungi were found to decrease significantly with land use intensification (Gherghel et al 2014). The comparison of perennial cropland sites with the secondary forest and fallow land showed a lower value of the Shannon diversity index of AM fungi for cropland (Snoeck et al 2010).…”
Section: Species Richness and Diversitysupporting
confidence: 61%
See 1 more Smart Citation
“…Similar to the total species richness estimates, diversity estimates based on the Shannon index of AM fungi (Honnay et al 2017), ECM fungi and total fungi were found to decrease significantly with land use intensification (Gherghel et al 2014). The comparison of perennial cropland sites with the secondary forest and fallow land showed a lower value of the Shannon diversity index of AM fungi for cropland (Snoeck et al 2010).…”
Section: Species Richness and Diversitysupporting
confidence: 61%
“…For instance, during the conversion of forested areas to cropland, or to perennial cropland and fallow land (Tchabi et al 2008), a reduction in the AM fungal richness was found. Likewise, when analyzing ECM fungal richness in roots of poplar plants in different land use (former cropland, former grassland, and former spruce stand), lower ECM fungal richness was found in former cropland sites compared to that found in the former spruce forest or former grassland (Gherghel et al 2014). Although a decrease in species/OTUs richness values were common after increasing land use intensity, some contrasting results were also observed.…”
Section: Species Richness and Diversitymentioning
confidence: 89%
“…On lower fertility sites, it may be advantageous for poplars to allocate more belowground biomass to build a larger coarse root system for storage purposes. Stored carbohydrates and amino acids in roots could then be used locally, and in timely fashion, to sustain a higher level of fine root growth, symbiotic associations with fungi [80,81] and root exudation [82,83]. These three processes have an increasing importance for nutrient capture as site fertility decreases [84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome composition in plant tissues can be genotype-dependent and significantly different from the microbiome composition in the rhizosphere [1,3,17,19]. The role of plant genotypes in shaping the biomass and community structure of the mycorrhizal part of the microbial community has also been reported by Corredor et al [20], Gehring et al [21], Gherghel et al [22], Karliński et al [23,24], and Tagu et al [25]. Most of these findings indicate that tree genotype affects the process of recruitment of ectomycorrhizal fungi in the soil by influencing both the quantities of organic compounds released from the roots and the profiles of root exudates [26].…”
Section: Introductionmentioning
confidence: 89%